ANALISIS PENGARUH KEBIJAKAN DIVIDEN, KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016: ANALISIS PENGARUH KEBIJAKAN DIVIDEN, KEPEMILIKAN INSTITUSIONAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP KEBIJAKAN HUTANG PADA PERUSAHAAN PROPERTY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2016 - Hayati, Keumala (JURNAL MUTIARA AKUNTANSI, 2017)
The purpose of this research is to analyze dividend policy, institutional ownership, company size, and profitability to debt policy on property companies listed on BEI period 2014-2016. Debt policy was measure by Debt to Equity Ratio. The population of this research is 47 companies based on purposive sampling method, there are 16 samples as the object of research with 48 units analize. This research use the annual report and financial reporting of each company that published in www.idx.co.id and using multiple regression analysis. The result of this research shows that simultaneous had significant effect to debt policy. At partially test showed that dividend policy and profitability had negatif signifikan to debt policy, and institutional ownership, company size had not effect to debt policy.Keywords: dividend policy, institutional ownership, company size, company size, profitability, debt policy